ANNUAL AND SEMI-ANNUAL VARIATIONS OF THE GPS-DERIVED PRECIPITABLE WATER VAPOR OVER SUMATRA ISLAND - Dudy D. Wijaya; Nabila S.E. Putri; Yan A. Rahmawan; Sidik T. Wibowo; Akhmad Y. Basuki; Muhammad S. Fathulhuda; Vera Sadarviana (Jurnal Meteorologi dan Geofisika, 2021)
We have utilized the Global Positioning System (GPS) data at 57 stations distributed over Sumatra Island to investigate spatio-temporal variations of the atmospheric precipitable water vapor (PWV). We focused on the annual and semi-annual cycles of the PWV. Our results show that Sumatra Island is divided into two distinct areas of annual and semi-annual cycles, where the boundary line between the areas is approximately at 2oS. While the annual cycle dominates the area over the southern side of 2oS, the semi-annual cycle is dominant over the northern side. Our results have further shown that the maximum phase of annual cycle occurs between January-March with considerably large amplitudes (10-15 mm). On the other side, the maximum phase of the semi-annual cycle in general occurs around November and May, whose amplitude is approximately between 1-5 mm. Our results are consistent with other results using rainfall data.